Pembuatan Alat Pengiris Bawang Kapasitas 50 kg/jam - Tampubolon, Deo G; Hermanto, Tino; Rokhim, Mochamad Iqbal (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
This study aims to design and implement a shallot slicing machine with a 50 kg/hour capacity to improve production efficiency among food-sector MSMEs. The machine features an elbow-iron frame, a 0.5 HP electric motor, and a pulley-V belt transmission system driving stainless steel blades. Performance testing evaluated actual capacity, transmission stability, and slice uniformity. Results show the machine operates stably with near-target capacity and produces relatively consistent slices. The estimated cost of IDR 6,700,000 is economical for small businesses. The design’s strength lies in its simplicity, hygienic materials, and affordability. This machine is expected to offer an appropriate technological solution to enhance productivity and product quality in shallot processing.